2009
DOI: 10.1111/j.1477-9552.2008.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Production Efficiency of Jasmine Rice Producers in Northern and North‐eastern Thailand

Abstract: The paper jointly evaluates the determinants of switching to Jasmine rice and its productivity while allowing for production inefficiency at the level of individual producers. Model diagnostics reveal that serious selection bias exists, justifying use of a sample selection framework in stochastic frontier models. Results from the probit variety selection equation reveal that gross return (mainly powered by significantly higher Jasmine rice price), access to irrigation and education are the important determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 21 publications
7
41
1
Order By: Relevance
“…The size of the area under cultivation has an estimated parameter close between 0.23 and 0.29, consistent with those reported in other studies [50][51][52]. The lowest values are related to labor, L, around 0.11, consistent with the results from Rahman et al [53] and Mariano et al [52].…”
Section: Production Frontierssupporting
confidence: 82%
See 1 more Smart Citation
“…The size of the area under cultivation has an estimated parameter close between 0.23 and 0.29, consistent with those reported in other studies [50][51][52]. The lowest values are related to labor, L, around 0.11, consistent with the results from Rahman et al [53] and Mariano et al [52].…”
Section: Production Frontierssupporting
confidence: 82%
“…Our analysis, reveals a positive association between farm size and TE levels. There is evidence supporting the notion that large farms have higher levels of efficiency, due to advantages derived from economies of scale [49,53,54,60,63,66,71,72]. Considering the high percentage of small farms in the area under study, 28.6% according to ODEPA, which is the Chilean National Service for Agricultural Policy (the acronym stands for Oficina de Estudios y Políticas Agrarias) [72], this factor is likely a barrier to improve productivity levels in the region.…”
Section: Variablesmentioning
confidence: 99%
“…In a recent article, Rahman et al (2009) used the Greene (2010) model to analyze production efficiency for a sample of rice producers in Thailand. The authors analyzed the switch from lower quality rice varieties to Jasmine rice which is a higher quality product.…”
Section: Related Literaturementioning
confidence: 99%
“…Their results indicate that the correction for adoption of the higher quality variety produced marked differences in the estimated production frontier and a highly significant "selection effect". However, Rahman et al (2009) did not use any matching techniques to ensure that the control and treated groups had similar observed characteristics.…”
Section: Related Literaturementioning
confidence: 99%
“…The farmers who received training provided by extension department were more efficient than that of the farmers who did not. Many researchers reported that the extension work move the inefficient farmers to closer to the frontier (Balcombe et al 2007;Rahman et al, 2009;Coelli et al, 2003;Rahman, 2003 andMyint andKyi, 2005).However, Coelli et al (2002) concluded that farmers" age, education, experience; extension and training do not have large influence on efficiency level. So, it can be concluded that extension service by training is superior to extension contact.…”
Section: Description Of Datamentioning
confidence: 99%